Vibrio parahaemolyticus strengthen their virulence through modulation of cellular Reactive Oxygen Species in-vitro - El-Malah, Shimaa S.; Yang, Zhenquan; Hu, Maozhi; Li, Qiuchun; Pan, Zhiming; Jiao, Xinan (Frontiers in Cellular and Infection Microbiology, 2014)
Vibrio parahaemolyticus (Vp) is one of the emergent food-borne pathogens that are commensally associated with various shellfish species throughout the world. It is strictly environmental and many strains are pathogenic to humans, the virulent strains causes distinct diseases, including wound infections, septicemia, and most commonly, acute gastroenteritis, which is acquired through the consumption of raw or undercooked seafood, especially shellfish. Vp has two type three secretion systems (T3SSs), which triggering its cytotoxicity and enterotoxicity via their effectors. To better understand, the pathogenesis of Vp we established cell infection model in-vitro using a non-phagocytic cell line. Caco-2 cells were infected with different strains of Vp (pandemic and non-pandemic strains) and several parameters of cytotoxicity, were measured, together with, adhesion and invasion indices which reflect the pathogen’s virulence. Our results show that Vp, adheres to cell monolayers and can invade non-phagocytic cells. It also survives and persists in non-phagocytic cells by modulating reactive oxygen species (ROS), allowing its replication and, resulting in complete cellular destruction. We conclude that the pathogenicity of Vp is based on its capacities for adhesion and invasion, surprisingly's; enhanced of ROS resistance period could promote the survival of Vp inside the intestinal tract, facilitating tissue infection by repressing the host’s oxidative stress response.